Determinants of feeding practices and growth of Filipino infants a longitudinal study - Nguyen, Trung Tin
This study is a secondary analysis of a prospective cohort study composed of 2,265 normal birthweight infants followed up over a period of one year. Outcome variables are breastfeeding practices and anthropometric measurement (such as weight and height which are measured at birth or 7 days, and at 2, 4, 6, 8, 10 and 12 months).